2007
DOI: 10.1186/1471-2164-8-317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogenomic analyses of teleost fish Hox gene clusters: lessons from the cichlid fish Astatotilapia burtoni

Abstract: BackgroundTeleost fish have seven paralogous clusters of Hox genes stemming from two complete genome duplications early in vertebrate evolution, and an additional genome duplication during the evolution of ray-finned fish, followed by the secondary loss of one cluster. Gene duplications on the one hand, and the evolution of regulatory sequences on the other, are thought to be among the most important mechanisms for the evolution of new gene functions. Cichlid fish, the largest family of vertebrates with about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 97 publications
8
81
0
Order By: Relevance
“…Primers for Hox genes were designed based on published Oreochromis niloticus (Nile tilapia) cDNA sequences (Santini and Bernardi, 2005), or genomic Astatotilapia burtoni sequences (Hoegg et al, 2007). Primers for fli-1, pea-3 and dlx2a were designed based on genomic sequence comparisons of each gene between Gasterosteus aculeatus (three-spined stickleback), Takifugu rubripes, Oryzias latipes (japanese medaka), and Danio rerio (zebrafish).…”
Section: Molecular Marker Cloningmentioning
confidence: 99%
See 2 more Smart Citations
“…Primers for Hox genes were designed based on published Oreochromis niloticus (Nile tilapia) cDNA sequences (Santini and Bernardi, 2005), or genomic Astatotilapia burtoni sequences (Hoegg et al, 2007). Primers for fli-1, pea-3 and dlx2a were designed based on genomic sequence comparisons of each gene between Gasterosteus aculeatus (three-spined stickleback), Takifugu rubripes, Oryzias latipes (japanese medaka), and Danio rerio (zebrafish).…”
Section: Molecular Marker Cloningmentioning
confidence: 99%
“…Although expression of hoxa3a and hoxa4a has not been reported in zebrafish, recent evidence from conditional deletion of the mouse Hoxa cluster in NC cells suggests that Hoxa cluster genes have a primary role in the biology of skeletogenic NC cells in mice (Minoux et al, 2009). Because all PG1 to PG8 genes, except for hoxa2b, have been lost from the teleostean hoxab cluster (Hoegg et al, 2007), it is likely that functions carried by the ancestral osteichthyan hoxa cluster were mostly inherited by the teleostean hoxaa cluster. Studies of zebrafish hoxa3a and a4a expression are needed to explore this possibility, and functional studies in zebrafish and tilapia will tell whether genes of the hoxaa cluster have a dominant role in specifying the PJA skeleton.…”
Section: Hox Patterning Of the Pharyngeal Jaw Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, Hox cluster genes also exhibit temporal collinearity; that is, genes located in the 3Ј-end of the cluster are expressed early during development, whereas genes in the 5Ј-end are expressed later (2). Recent comparative studies of Hox clusters in model genomes have shown that Hox clusters have experienced repeated molecular changes, including fragmentation, cluster duplication, gene loss, coding-sequence divergence, and cisregulatory element evolution (3)(4)(5)(6)(7). Because of their critical role in defining the identities of body segments, Hox genes are believed to have played a key role in driving the morphologic diversification of animals (8)(9)(10) and thus are of particular interest in understanding the genetic basis of morphologic diversity of metazoans.…”
mentioning
confidence: 99%
“…Whereas a duplicate HoxD cluster is lost in zebrafish, acanthopterygians such as fugu, medaka, and cichlids have lost a duplicate HoxC cluster. In addition, several Hox genes have experienced lineagespecific secondary losses resulting in each of these teleosts possessing a unique set of Hox genes (5,15). In contrast to these teleosts, Atlantic salmon contains as many as 13 Hox clusters owing to an additional genome duplication in a salmonid ancestor (16).…”
mentioning
confidence: 99%